A retrospective record review of mental health care users who abscond from a psychiatric hospital - Arbee, Feroza (My University, 2014)
Introduction Absconding from psychiatric facilities has socioeconomic implications. The aetiology is multifactorial. Absconding patients are at higher risk of self-harm, violence, non-adherence, relapses, substance use and negative media attention. Identification of potential absconders would assist with risk assessment and prevention. Methods A retrospective record review was conducted of all absconds from a tertiary psychiatric hospital over one year. An abscond rate and a profile were formulated. In addition, trends were identified since the inception of democracy and deinstitutionalization. Results 97 patients absconded 108 times during the study period, 7 having absconded more than once. The absconding rate was 7.83%. The typical absconder is: single, unemployed male, in his early 30’s, known to psychiatric services, diagnosed with schizophrenia and co-morbid substance use. The typical absconder is more likely to be a forensic patient not returning from an official leave of absence. Conclusion The study defines the profile of the typical absconder. The abscond rate has decreased to half that of a previous study by Siwinska (1993). Mental health care users are being treated in a less restrictive manner and this results in less absconds and a change in the method of absconds. This has implications for clinical practice.
Thesis (M.Med.(Psychiatry))--University of the Witwatersrand, Faculty of Health Sciences, 2014.
Keywords: Hospitals, Psychiatric--South Africa; Patient Dropouts